Perancangan Tempat Penyimpanan WIP untuk Meminimasi Cacat Size Mismatching pada Kaus dengan Menggunakan Metode NIDA (Need, Ideas, Decision, Action) Pada PT Fluxdev Global Industry - Puspitasari, Indah; Andias Anugraha, Rino; Poeri Suryadhini, Pratya (Dinasti Research, 2024)
A small and medium-sized company in the t-shirt manufacturing industry, PT Fluxdev Global Industry, is having trouble achieving its production goals. The primary issue is that the components of the socks that are made don't match in size. The fact that the chopped materials are not sorted by size is one of the contributing reasons, since it makes it challenging for the operator to determine the size of the materials to be processed. According to the Lean Six Sigma methodology, the company's process capability index (Cp) only reached 1.30 as a result of the inability to satisfy production targets. Even if the production method is very competent, more advancements are still required to increase this index in order to meet the company's goals. In order to minimize product defects, the proposed improvement in this Final Project is to design a tool that can address these issues. The focus of this improvement is to avoid the accumulation of materials after cutting by separating the materials based on size. The design of the assistive device is carried out using the NIDA method. (Needs, Ideas, Decision, Action). The designed aid is a trolley with dividers to separate the sizes of garment components such as S, M, L, and XXXL. This trolley comes in two sizes, 100 x 71 cm and 110 x 71 cm, and is designed to facilitate operators in sorting and identifying the sizes of body and sleeve components according to the cutting patterns.